(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article provides a comprehensive comparative and typological analysis of word order in French and Uzbek. The study examines the syntactic structure of both languages, the positional patterns of sentence constituents, and the grammatical, semantic, and pragmatic functions of word order based on scholarly sources and illustrative examples. French is analyzed as an analytic language with a relatively fixed word order, whereas Uzbek is characterized as an agglutinative language with a relatively free word order. Special attention is given to the role of word order in information structure (theme–rheme), pragmatic emphasis, and translation processes. The findings of the study are of theoretical and practical significance for comparative linguistics, translation studies, and foreign language teaching methodology.